Composite modified negative electrode material and preparation method and application thereof

Through the composite modification of Mn2Si(P2O7)2 nanomaterials, nanosilicon and layered graphite, the structural destruction problem caused by volume change of Si-based negative electrode materials was solved, and the cycle stability and electrochemical performance of the battery were improved.

CN120356932BActive Publication Date: 2025-10-10GANZHOU NUOWEI NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510837886.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-10-10
Estimated Expiration
2045-06-23

AI Technical Summary

Technical Problem

Existing Si-based negative electrode materials undergo large volume changes during the electrochemical process, which leads to damage to the electrode structure and degradation of battery performance, affecting the electrochemical performance.

Method used

Mn2Si(P2O7)2 nanomaterials, nanosilicon and layered graphite are used for composite modification. Mn2Si(P2O7)2 nanomaterials are synthesized by liquid phase co-precipitation method and solid phase mixed with nanosilicon and layered graphite to form Si-Si covalent bonds, inhibit nanosilicon aggregation, and improve structural stability and conductivity.

Benefits of technology

It effectively alleviates the volume expansion of the silicon negative electrode, improves the cycle performance of the negative electrode material and the electrochemical performance of the battery, and enhances the mechanical properties and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120356932B_ABST
    Figure CN120356932B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery materials, and discloses a composite modified negative electrode material and a preparation method and application thereof, the composite modified negative electrode material comprises Mn2Si(P2O7)2 nanomaterial, nanosilicon and layered graphite, and the Mn2Si(P2O7)2 nanomaterial, the nanosilicon and the layered graphite material are uniformly distributed. The composite modified negative electrode material has good structural stability, meanwhile, the silicon element in the pyrophosphosilicate in the negative electrode material and the nanosilicon can form Si-Si covalent bonds, can greatly improve the adhesion of the surface composite layer of the negative electrode material, and can inhibit the aggregation of the nanosilicon, and then can relieve the volume expansion of the silicon negative electrode, and can improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of lithium ion battery materials, and relates to a negative electrode material in a lithium ion battery material, in particular to a composite modified negative electrode material and a preparation method and application thereof. BACKGROUND

[0002] Lithium ion batteries have high specific energy, long service life, high working voltage, wide use temperature range, no memory effect, small self-discharge and environmental friendliness, and are therefore widely used in new energy vehicles, power grid energy storage and portable electronic devices. In order to improve the specific energy of lithium ion batteries, two aspects of the internal structure and materials of lithium ion batteries are usually considered. The optimization direction of the internal structure is mainly to reduce the weight of structural parts, copper foil, aluminum foil and other non-active materials, thereby increasing the proportion of active materials and improving the specific energy of lithium ion batteries. The optimization direction of the material is mainly to develop positive and negative electrode materials with higher capacity and positive electrode materials with higher voltage, so as to improve the capacity and voltage of the battery and achieve the purpose of improving the energy of the battery.

[0003] At present, the development direction of negative electrode materials is mainly to improve the capacity of the material. For example, the Si-based material with relatively mature technology can achieve a capacity of more than 1000 mAh / g by ammonia doping graphite-based materials or doping metal sulfides, which is much higher than that of graphite-based materials. However, the Si-based material has a large volume change in the electrochemical process, which easily leads to irreversible phase change of silicon particles, thereby causing damage to the electrode structure and degradation of the battery performance, and affecting the electrochemical performance of the battery. SUMMARY

[0004] In view of the defects and deficiencies of the prior art, in a first aspect, the application provides a composite modified negative electrode material, in a second aspect, the application provides a preparation method of the composite modified negative electrode material, and in a third aspect, the application provides a battery.

[0005] In a first aspect, the application provides a composite modified negative electrode material, which comprises Mn2Si(P2O7)2 nanomaterial, nanosilicon and layered graphite, wherein the Mn2Si(P2O7)2 nanomaterial, the nanosilicon and the layered graphite material are uniformly distributed.

[0006] Preferably, the mass ratio of the Mn2Si(P2O7)2 nanomaterial, the nanosilicon and the layered graphite is 1:1-2:0.01-0.05.

[0007] In a second aspect, the application provides a preparation method of the composite modified negative electrode material, which comprises the following steps:

[0008] Step 1: Add a soluble silicate to concentrated phosphoric acid to react to obtain a gel solution A, then add the gel solution A to a soluble manganese salt solution to obtain a gel solution B. After reacting for a certain period of time, the solution is filtered, and the filter cake is washed with water, washed with alcohol, and dried to obtain solid particles, which are Mn2Si(P2O7)2 nanomaterials.

[0009] Step 2: ball milling and mixing the Mn2Si(P2O7)2 nanomaterial, nano-silicon and layered graphite to obtain the composite modified negative electrode material.

[0010] Preferably, the soluble silicate is any one or more of sodium silicate, potassium silicate and lithium silicate.

[0011] Preferably, the mass concentration of the concentrated phosphoric acid is 75% to 85%.

[0012] Preferably, the soluble manganese salt is any one or more of manganese nitrate, manganese sulfate and manganese acetate.

[0013] Preferably, the molar ratio of silicate ions, manganese ions and phosphate ions in the gel solution B is 1:2.03-3:4.01-4.03.

[0014] Preferably, in step 1, the reaction time of the soluble silicate and concentrated phosphoric acid is 5 to 30 minutes.

[0015] Preferably, in step 1, the reaction time after adding the soluble manganese salt to the gel solution A to obtain the gel solution B is 6 to 12 hours.

[0016] Preferably, in step 2, the mass ratio of the Mn2Si(P2O7)2 nanomaterial, the nano-silicon and the layered graphite is 1:1~2:0.01~0.05.

[0017] Preferably, in step 2, the ball milling mixing time is 1 to 6 hours, and the ball milling speed is 200 to 300 r / min.

[0018] In a third aspect, the present invention provides a battery comprising the above-mentioned composite modified negative electrode material or the composite modified negative electrode material prepared by the above-mentioned preparation method.

[0019] Compared with the prior art, the present invention has the following obvious beneficial effects:

[0020] (1) The composite modified negative electrode material provided by the present invention has good structural stability. At the same time, the silicon element in the pyrophosphate silicate in the negative electrode material and the nano-silicon can form Si-Si covalent bonds, which can greatly improve the adhesion of the composite layer on the surface of the negative electrode material and inhibit the aggregation of nano-silicon, thereby alleviating the volume expansion of the silicon negative electrode and improving the cycle performance of the battery.

[0021] (2) The present invention synthesizes pyrophosphate silicate Mn2Si(P2O7)2 nanomaterials by liquid phase coprecipitation method, and then solid-phase mixes it with nano-silicon and layered graphite to prepare Mn2Si(P2O7)2 / Si@C negative electrode materials. The process is simple and controllable, does not require roasting, consumes low energy, and is conducive to promotion and commercialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is an SEM image of the composite modified negative electrode material prepared in Example 1;

[0023] Figure 2 The graph shows the cycle performance test of batteries assembled with the negative electrode materials and nano-silicon prepared in Examples 1 to 3 and Comparative Examples 1 to 3;

[0024] Figure 3 This is a SEM image of the electrode sheet made from the negative electrode material prepared in Example 1 before participating in battery cycling;

[0025] Figure 4 This is an SEM image of the electrode sheet made of the negative electrode material prepared in Example 1 after participating in 50 battery cycles;

[0026] Figure 5 This is a SEM image of the electrode sheet made from the negative electrode material prepared in Comparative Example 1 before participating in battery cycling;

[0027] Figure 6 This is an SEM image of the electrode sheet made from the negative electrode material prepared in Comparative Example 1 after 50 cycles of battery cycling. DETAILED DESCRIPTION

[0028] The present invention provides the following specific technical solutions.

[0029] In the first aspect, the present invention provides a composite modified negative electrode material, comprising Mn2Si(P2O7)2 nanomaterial, nanosilicon and layered graphite, wherein the Mn2Si(P2O7)2 nanomaterial, nanosilicon and layered graphite material are uniformly distributed.

[0030] Silicon as an anode material has significant advantages in lithium-ion batteries. Silicon anode can store more lithium ions, thereby improving the energy density and endurance time of the battery. However, silicon in practical applications faces some challenges, such as the huge volume change during charging and discharging, which can lead to the destruction of the electrode structure and the attenuation of the battery performance. Therefore, although silicon has high capacity advantages, its cycle stability is weak, which limits its wide application in battery anode materials. The inventors found that by adding pyrophosphate silicate and layered graphite to the anode material, the first aspect, pyrophosphate silicate has good structural stability, which can greatly improve the mechanical properties of the overall anode material. At the same time, after ball milling, it is in close contact with nano-silicon, which can not only effectively inhibit the agglomeration of nano-silicon, but also can relieve the volume expansion of the silicon anode through the interparticle interaction force. The second aspect, the layered graphite has good electronic conductivity and lubricity. Adding layered graphite to the anode material can not only effectively increase the conductivity of the anode material, thereby improving the reaction kinetics of the electrode material, but also can improve the uniformity of the composite material by using the lubricity of the layered graphite. The third aspect, nano-silicon and layered graphite and Mn2Si(P2O7)2 nanomaterials exhibit good compatibility and synergistic effect. Layered graphite, nano-silicon and Mn2Si(P2O7)2 nanomaterials can complement each other in lithium storage mechanism, and together optimize the comprehensive performance of the anode material, which has outstanding performance in electrochemical performance, mechanical properties and other aspects, and can synergistically optimize the large rate cycle stability and reversibility of the silicon anode material, and is more suitable for the application requirements of high-performance batteries.

[0031] Preferably, the mass ratio of the Mn2Si(P2O7)2 nanomaterial, the nano-silicon and the layered graphite is 1:1~2:0.01~0.05.

[0032] Secondly, the application provides a preparation method of the composite modified anode material, comprising the following steps:

[0033] Step 1, a soluble silicate is added to concentrated phosphoric acid to obtain a gel solution A, then the gel solution A is added to a soluble manganese salt solution to obtain a gel solution B, and after a certain reaction time, the filter cake is washed with water, alcohol and dried to obtain the solid particles, which are the Mn2Si(P2O7)2 nanomaterials;

[0034] Step 2, ball-mixing the Mn2Si(P2O7)2 nanomaterials, nano-silicon and layered graphite to obtain the composite modified anode material.

[0035] After research, the inventors found that the synthesis of pyrophosphate silicate Mn2Si(P2O7)2 nanomaterials by liquid phase co-precipitation method has uniform composition, small particle size and no agglomeration phenomenon, and the product has stable performance, which is conducive to the subsequent mixing of nano-silicon and layered graphite, and the various components in the final negative electrode material are evenly dispersed.

[0036] In practical applications, the layered graphite can be either natural graphite material or artificial graphite material, as long as the graphite used has a layered structure.

[0037] Preferably, the soluble silicate is any one or more of sodium silicate, potassium silicate and lithium silicate.

[0038] Preferably, the mass concentration of the concentrated phosphoric acid is 75% to 85%.

[0039] Preferably, the soluble manganese salt is any one or more of manganese nitrate, manganese sulfate and manganese acetate.

[0040] Preferably, the average particle size of the nano-silicon is 50-100 nm.

[0041] Preferably, the thickness of the layered graphite is 0.3-0.6 nm.

[0042] Preferably, the molar ratio of silicate ions, manganese ions and phosphate ions in the gel solution B is 1:2.03-3:4.01-4.03.

[0043] In practical applications, the addition ratio of phosphate ions is consistent with the stoichiometric ratio, with a slight excess being acceptable to ensure complete phosphate complexation. Excessive excess will subsequently react with manganese ions to form manganese phosphate precipitates, affecting product performance. The above ratio represents a preferred range, where the formation of other impurities is avoided, which is beneficial for improving the electrochemical performance of the negative electrode material.

[0044] Preferably, in step 1, the reaction time after adding the soluble manganese salt to the gel solution A to obtain the gel solution B is 6 to 12 hours.

[0045] Preferably, in step 2, the mass ratio of the Mn2Si(P2O7)2 nanomaterial, the nano-silicon and the layered graphite is 1:1~2:0.01~0.05.

[0046] Preferably, in step 2, the ball milling mixing time is 1 to 6 hours, and the ball milling speed is 200 to 300 r / min.

[0047] In a third aspect, the present invention provides a battery comprising the above-mentioned composite modified negative electrode material or the composite modified negative electrode material prepared by the above-mentioned preparation method.

[0048] In order to make the technical problems, technical solutions and technical advantages to be solved by the present application more clear, the following will be described in detail in combination with specific examples, but the protection scope of the present application is not limited to the following specific examples.

[0049] Unless otherwise defined, all the professional terms used in the following have the same meaning as generally understood by the person skilled in the art. The professional terms used in the present application are only for the purpose of describing the specific examples, and are not intended to limit the protection scope of the present application.

[0050] Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in the present application can be purchased from the market or can be prepared by the existing method.

[0051] Example 1:

[0052] A preparation method of a composite modified negative electrode material, comprising the following steps:

[0053] Step 1: 0.1 mol of sodium silicate is added to 26.33 mL of 80% mass concentration phosphoric acid, and a uniform dispersion gel solution A is obtained by composite reaction at room temperature of 25℃ for 10 min, then the gel solution A is added to 110 mL of 2 mol / L manganese nitrate solution, and after reaction at room temperature for 8 h, filtration, water washing, alcohol washing and drying are sequentially performed, and the obtained solid particles are Mn2Si(P2O7)2 nanomaterials;

[0054] Step 2: 0.3 g of Mn2Si(P2O7)2 nanomaterials, 15 g of nanosilicon and 10 g of layered graphite are ball-mixed for 4 h, and the D50 of the nanosilicon is 80 nm, so that the composite modified negative electrode material is prepared.

[0055] Figure 1 The SEM image of the composite modified negative electrode material prepared in Example 1 is shown in the following figure: Figure 1 It can be seen that the overall material morphology is spherical, and the particle size is uniform.

[0056] Comparative Example 1:

[0057] A preparation method of a negative electrode material, comprising: 10 g of layered graphite and 15 g of nanosilicon (80 nm) are ball-mixed for 4 h, so that the Si / C negative electrode material is prepared.

[0058] Comparative Example 2:

[0059] A preparation method of a composite modified negative electrode material, comprising the following steps:

[0060] Step 1: 0.1 mol of sodium silicate was added to 26.33 mL of 80% concentrated phosphoric acid, and the mixture was reacted at room temperature of 25°C for 10 minutes to obtain a uniform gel solution A. Solution A was then added to 100 mL of a 2 mol / L manganese nitrate solution, and the mixture was reacted for 8 hours. After filtration, washing with water, washing with alcohol, and drying, the obtained solid particles were Mn2Si(P2O7)2 nanomaterials.

[0061] Step 2: Take 0.3g of Mn2Si(P2O7)2 nanomaterial and 10g of layered graphite and ball-mill them for 4h to obtain Mn2Si(P2O7)2 / C negative electrode material.

[0062] Comparative Example 3:

[0063] A method for preparing a composite modified negative electrode material comprises the following steps:

[0064] Step 1: 0.1 mol of sodium silicate is added to 26.33 mL of 85% concentrated phosphoric acid, and the mixture is reacted at room temperature of 25°C for 10 minutes to obtain a uniform gel solution A. Solution A is then added to 100 mL of a 2 mol / L manganese nitrate solution, and the mixture is reacted for 8 hours. The mixture is filtered, washed with water, washed with alcohol, and dried in sequence to obtain solid particles of Mn2Si(P2O7)2 nanomaterials.

[0065] Step 2: Take 0.3g of Mn2Si(P2O7)2 nanomaterial and 15g of nanosilicon (80nm) and mix them by ball milling for 4h to obtain Mn2Si(P2O7)2 / Si negative electrode material.

[0066] Example 2:

[0067] A method for preparing a composite modified negative electrode material comprises the following steps:

[0068] Step 1: Add 0.1 mol of lithium silicate to 28.03 mL of 75% concentrated phosphoric acid, and react at room temperature of 25°C for 30 minutes to obtain a uniform gel solution A. Then, add solution A to 203 mL of 1 mol / L manganese nitrate solution, react at room temperature for 6 hours, filter, wash with water, wash with alcohol, and dry to obtain Mn2Si(P2O7)2 nanomaterial.

[0069] Step 2: Take 0.1g of Mn2Si(P2O7)2 nanomaterial, 10g of nanosilicon and 10g of layered graphite and ball-mill them for 1h. The D50 of nanosilicon is 50nm, and a composite modified negative electrode material can be obtained.

[0070] Example 3:

[0071] A method for preparing a composite modified negative electrode material comprises the following steps:

[0072] Step 1, 0.1 mol of lithium silicate was added into 24.85 mL of concentrated phosphoric acid with a mass concentration of 85%, and a room temperature composite reaction was carried out for 5 min to obtain a uniform gel solution A, then solution A was added into 100 mL of a manganese acetate solution with a concentration of 3 mol / L, and a room temperature reaction was carried out for 12 h, and after filtration, water washing, alcohol washing and drying, Mn2Si(P2O7)2 nanomaterials were obtained.

[0073] Step 2, 0.5 g of the Mn2Si(P2O7)2 nanomaterials prepared in step 1, 10 g of nanosilicon and 20 g of layered graphite were ball-milled and mixed for 6 h, and the D50 of the nanosilicon was 100 nm, so that the composite modified negative electrode material was prepared.

[0074] The negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 were used as active materials, which were mixed with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) at a mass ratio of 7:2:1, N-methyl pyrrolidone (NMP) was used as a solvent, and the mixture was stirred at a speed of 800 r / min in a small beaker for 2 h to obtain a slurry. The slurry was coated on a current collector aluminum foil using an automatic coating machine, placed on a tempered glass and dried in a vacuum drying oven at 85℃ for 4 h, and then punched into a 14 mm diameter electrode after being dried at 105℃ in a vacuum drying oven for 4 h. The electrode was placed in a glove box filled with argon gas atmosphere with water content and oxygen content less than 0.1 ppm for 4 h to reduce the adsorbed water in the transfer process, and then assembled into a CR2032 type button cell in the glove box. The separator used in the battery was a 18 mm diameter porous polyethylene film with a model of Celgard2300, and lithium sheet was used as the counter electrode.

[0075] After the battery was assembled and aged for 12 h, a 2C rate charge-discharge test was carried out in a voltage range of 0.1-3.0 V.

[0076] Figure 2 The cycle performance test diagram of the battery assembled by the negative electrode material and nanosilicon prepared in Examples 1-3 and Comparative Examples 1-3 is shown in FIG. 2. Figure 2 It can be seen that the negative electrode material provided by the application is modified by pyrophosphate silicate and carbon material simultaneously, which can effectively improve the cycle performance of the silicon material.

[0077] Figure 3 The SEM diagram of the electrode prepared by the negative electrode material prepared in Example 1 before participating in the battery cycle is shown in FIG. 3. Figure 3 It can be seen that the thickness of the electrode before participating in the cycle is about 8.6 μm. Figure 4 The SEM diagram of the electrode prepared by the negative electrode material prepared in Example 1 after participating in the battery cycle for 50 cycles is shown in FIG. 4. Figure 4 It can be seen that the thickness of the electrode after participating in the cycle is about 9.7 μm.

[0078] Figure 5 The SEM image of the electrode sheet prepared from the negative electrode material prepared in Comparative Example 1 before participating in the battery cycle is shown in FIG. 1. Figure 5 It can be seen that the thickness of the electrode sheet before participating in the cycle is about 11.4 μm. Figure 6 The SEM image of the electrode sheet prepared from the negative electrode material prepared in Comparative Example 1 after participating in the battery cycle for 50 cycles is shown in FIG. 2. Figure 6 It can be seen that the thickness of the electrode sheet after participating in the cycle is about 17.9 μm.

[0079] In combination with Figures 3-6 It can be proved that the electrode sheet prepared from the negative electrode material prepared in the present application has good structural stability, can greatly relieve the volume expansion of the electrode sheet, and improve the electrochemical performance of the battery.

[0080] The above-described embodiments are merely preferred specific embodiments of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art, within the technical scope of the present application, according to the technical solution and concept of the present application, makes equivalent replacement or change, should be covered in the protection scope of the present application.

Claims

1. A composite modified negative electrode material, characterized in that: It comprises Mn2Si(P2O7)2 nanomaterials, nano-silicon and layered graphite, wherein the Mn2Si(P2O7)2 nanomaterials, nano-silicon and layered graphite are uniformly distributed.

2. The composite modified negative electrode material according to claim 1, characterized in that The mass ratio of the Mn2Si(P2O7)2 nanomaterial, the nano-silicon and the layered graphite is 1:1~2:0.01~0.

05.

3. A method for preparing a composite modified negative electrode material, characterized in that: The steps include: Step 1: Add a soluble silicate to concentrated phosphoric acid to react to obtain a gel solution A, then add the gel solution A to a soluble manganese salt solution to obtain a gel solution B. After reacting for a certain period of time, the solution is filtered, and the filter cake is washed with water, washed with alcohol, and dried to obtain solid particles, which are Mn2Si(P2O7)2 nanomaterials. Step 2: ball milling and mixing the Mn2Si(P2O7)2 nanomaterial, nano-silicon and layered graphite to obtain the composite modified negative electrode material.

4. The method for preparing the composite modified negative electrode material according to claim 3, wherein: The molar ratio of silicate ions, manganese ions and phosphate ions in the gel solution B is 1:2.03-3:4.01-4.

03.

5. The method for preparing the composite modified negative electrode material according to claim 3 or 4, characterized in that: In step 2, the mass ratio of the Mn2Si(P2O7)2 nanomaterial, the nano-silicon and the layered graphite is 1:1~2:0.01~0.

05.

6. The method for preparing the composite modified negative electrode material according to claim 3, wherein: The soluble silicate is any one or more of sodium silicate, potassium silicate and lithium silicate; the soluble manganese salt is any one or more of manganese nitrate, manganese sulfate and manganese acetate.

7. The method for preparing the composite modified negative electrode material according to claim 3, wherein: The mass concentration of the concentrated phosphoric acid is 75% to 85%.

8. The method for preparing the composite modified negative electrode material according to claim 3, wherein: In step 1, the reaction time after adding the soluble manganese salt to the gel solution A to obtain the gel solution B is 6 to 12 hours.

9. The method for preparing the composite modified negative electrode material according to claim 3 or 8, wherein: In step 2, the ball milling mixing time is 1 to 6 hours, and the ball milling speed is 200 to 300 r / min.

10. A battery, characterized in that: The invention comprises the composite modified negative electrode material according to any one of claims 1 to 2 or the composite modified negative electrode material prepared by the preparation method according to any one of claims 3 to 9.

Citation Information

Patent Citations

  • Silicon-based electrode material, negative electrode sheet, secondary battery, and electronic device

    CN116936783A

  • Modified negative electrode material, preparation method therefor, negative electrode plate, secondary battery, and electrical device

    US20250070173A1